(3HMhK GdYedjGJ hGSJNOGe MRe GdHQeLjGJ (B:s (3HQeLjI GdNhGQRej (B/s - (3GdTjN, YGUe YHO GdQMefs ((3YeGf(B: s (3OGQ GdefGgL ddfTQ hGdJhRjY(B, s, 1999)
(3HMhK GdYedjGJ hCSdhHgG aj Md GdeTGcd(B- (3GdHQeLjI GdNWjI(B- (3GdWQjbI GdHjGfjI(B- (3GdHQeLI GdNWjI(B- (3GdHQeLI GdNWjI hJMdjd GdMSGSjI hGdKfGFjI(B- (3GdMd HhGSWI GdMGShH hHYV GdJWHjbGJ(B- (3Gdfbd hGdJYjjf(B- (3JMdjd GdbQGQ(B- (3feGPL GdeNRhf(B- (3fXQjI GdUahas
Keywords: (3GdEYdGe GdCdjs; (3GdHQeLjGJs; (3Yde GdMGShHs